The influence of IT leaders’ leadership behavior on IT governance performance in higher Education: a literature review - Hussain, Waheed; Hussin, Husnayati; Mohamed Razi, Mohamed Jalaldeen (IEEE, 2018)
IT has become one of the most invested areas of organisations, especially in higher education institutions. To safeguard these IT investments and make the most out them, a good IT governance structure is required. It enables the higher education institutions to strive in the competition and to achieve strategic objectives. To have optimum governance in the institutions, IT leaders play the vital role of carrying the task of IT role models to implement the best approaches in the institutions. The purpose of this study is to explore the existing literature to find out the influence of IT leaders’ leadership behaviour on IT governance performance in higher education context. It is aimed to find the linkage between IT leaders’ leadership behaviour and IT governance performance in higher education to promote this area for future research. The literature review was done systematically to identify the articles relevant to the three variables, ‘IT governance’, ‘IT leadership’ and “higher education’. The results indicated that there is an influence of IT leadership behaviour on IT governance in higher education. Literature showed that improper IT leadership was perceived as a barrier to ITG, IT leadership plays a vital role in effective ITG implementation and specific leadership capacities and skills are shown to promote ITG. However, there are few studies in this area and there is a lack of knowledge on how IT leadership can influence IT governance.